2017
DOI: 10.1073/pnas.1702512114
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of avian haemosporidian assemblages through millennial time scales inferred from insular biotas of the West Indies

Abstract: Although introduced hemosporidian (malaria) parasites (Apicomplexa: Haemosporida) have hastened the extinction of endemic bird species in the Hawaiian Islands and perhaps elsewhere, little is known about the temporal dynamics of endemic malaria parasite populations. Haemosporidian parasites do not leave informative fossils, and records of population change are lacking beyond a few decades. Here, we take advantage of the isolation of West Indian land-bridge islands by rising postglacial sea levels to estimate r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Moreover, our data indicate that host switching rarely occurs between migratory and resident species occurring in sympatry during winter, despite the close phylogenetic relationship between many of the resident and migratory bird species. These patterns are intriguing, as previously published results suggest that haemosporidian parasites switch readily, even between distantly related hosts (Ellis et al, 2015;Ricklefs & Fallon, 2002;Ricklefs et al, 2014), and an analysis of haemosporidian assemblages in the West Indies reported essentially random switching of parasite lineages between host species perceived over millennial time scales (Soares et al, 2017).…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…Moreover, our data indicate that host switching rarely occurs between migratory and resident species occurring in sympatry during winter, despite the close phylogenetic relationship between many of the resident and migratory bird species. These patterns are intriguing, as previously published results suggest that haemosporidian parasites switch readily, even between distantly related hosts (Ellis et al, 2015;Ricklefs & Fallon, 2002;Ricklefs et al, 2014), and an analysis of haemosporidian assemblages in the West Indies reported essentially random switching of parasite lineages between host species perceived over millennial time scales (Soares et al, 2017).…”
Section: Discussionmentioning
confidence: 82%
“…Nonetheless, the geographic and host distributions of OZ14, OZ45, MI05 and KZ01 suggest that despite host mobility between breeding and wintering regions, some lineages transmitted on North American breeding grounds have not established transmission cycles in the Caribbean. Based on descriptions of parasite assemblages in resident hosts in the Caribbean region (Fallon et al, ; Ricklefs et al, ; Soares et al, ), Ecuador (Moens & Pérez‐Tris, ; Svensson‐Coelho et al, ), Colombia (González, Lotta, García, Moncada, & Matta, ; Pulgarín‐R et al, ) and Brazil (Fecchio et al, ), resident birds of the Neotropics appear to be either incompetent or suboptimal hosts for lineages that commonly occur in North America.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations